2016
DOI: 10.1037/gpr0000066
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Expectations and Relationship Quality

Abstract: This article reviews research that examines the effects of relationship expectations on interpersonal relationships. Most of the published research suggests that positive relationship expectations are associated with better interpersonal functioning, as indicated by greater relationship persistence, more positive relationship evaluations and motivations, more prorelationship behavior, more forgiveness, and reduced contempt. Research on related constructs, such as relationship efficacy, implicit theories, trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 153 publications
4
30
0
Order By: Relevance
“…Specifically, our findings suggest that attachment experiences from close relationships influence how leaders think of followers, and that underlying mechanisms include both a general effect (i.e., schema transference) and an additional effect that only involves avoidant leaders (i.e., defensive projection). This study is aligned with research on related psychological concepts, such as relationship expectations, relationship attributions, trust, and insecurity dispositions, finding that positive expectations, with a few exceptions, are associated with better interpersonal functioning (Lemay & Venaglia, 2016).…”
Section: Resultssupporting
confidence: 74%
“…Specifically, our findings suggest that attachment experiences from close relationships influence how leaders think of followers, and that underlying mechanisms include both a general effect (i.e., schema transference) and an additional effect that only involves avoidant leaders (i.e., defensive projection). This study is aligned with research on related psychological concepts, such as relationship expectations, relationship attributions, trust, and insecurity dispositions, finding that positive expectations, with a few exceptions, are associated with better interpersonal functioning (Lemay & Venaglia, 2016).…”
Section: Resultssupporting
confidence: 74%
“…Interestingly, in intergroup contexts, it is attachment anxiety, not avoidance, that has been related to hostile and avoidant reactions to outgroup members (Mikulincer & Shaver, 2001). Testing associations with both attachment dimensions would clarify the relational dynamics of contempt-proneness and help us understand the interpersonal motivations, expectations, and schemas that contempt-prone individuals bring to relationships (see also Lemay & Venaglia, in press). …”
Section: How Does Dispositional Contempt Relate To Other Dispositions?mentioning
confidence: 99%
“…Lemay (2016, p. 48) stated that "people pursue relationships that are expected to bring pleasure." Indeed, positive relationship expectations tend to enhance the functioning of romantic relationships (Burnette, McCullough, Van Tongeren, & Davis, 2012;Helgeson, 1994;Lemay, 2016;Lemay, Lin, & Muir, 2015;Lemay & Venaglia, 2016;Murray & Holmes, 1997). Studies have shown that constructive relationship behaviors are often guided by positive mental representations of the future (Baker, McNulty, & VanderDrift, 2017;Lemay, 2016;Lemay et al, 2015).…”
Section: The Influence Process: the Role Of Expectationsmentioning
confidence: 99%
“…Decision‐making theories posit that expectations for the future play a central role in shaping behavioral responses in interpersonal situations, such as romantic relationships (Gilbert & Wilson, ; Scheier & Carver, ). Lemay (, p. 48) stated that “people pursue relationships that are expected to bring pleasure.” Indeed, positive relationship expectations tend to enhance the functioning of romantic relationships (Burnette, McCullough, Van Tongeren, & Davis, ; Helgeson, ; Lemay, ; Lemay, Lin, & Muir, ; Lemay & Venaglia, ; Murray & Holmes, ). Studies have shown that constructive relationship behaviors are often guided by positive mental representations of the future (Baker, McNulty, & VanderDrift, ; Lemay, ; Lemay et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation